Prevalence of Work-Related Musculoskeletal Disorders in the Nurses Working in Hospitals of Xinjiang Uygur Autonomous Region - Ping Yan; Fuye Li; Li Zhang; Yi Yang; Amei Huang; Yanan Wang; Hua Yao (Pain Research and Management)
Objective. To investigate the status of work-related musculoskeletal disorders (WMSDs) in nurses working in the hospitals in Xinjiang Uygur Autonomous Region. Methods. The prevalence of WMSDs since working and in the previous 12 months was evaluated using self-administrated modified musculoskeletal questionnaire based on North European questionnaire. In this cross-sectional study, 6674 nurses involved in the nursing profession were selected from 16 hospitals using the stratified cluster sampling method. Results. The most commonly affected regions by WMSDs were lower back, neck, shoulder, and back, with an annual prevalence of 62.71%, 59.77%, 49.66%, and 39.50%, respectively. Statistical differences were noticed in the annual prevalence of WMSDs in those with different ages (P<0.01) and working durations (P<0.01). Logistic regression analysis indicated that the following risk factors were associated with the prevalence of WMSDs: working duration of ≥6 years; working in the Emergency Department, Department of Anesthesia, or Supply Room; night shift of more than once, working duration of >40 hrs per week; poor health status; and feeling of fatigue. Rest time of >10 min and no history of WMSDs were the protective factors of WMSDs. Conclusions. Shift and working/rest duration was closely related to WMSDs.